Comparison of good review practices of seven countries participating in the ECOWAS medicines regulatory harmonisation initiative: identifying opportunities for improvement - Owusu-Asante, Mercy; Darko, Delese Mimi; Seaneke, Seth; Nacoulma, Aminata; Traore, Oula Ibrahim Olivier; Adeyeye, Christianah Mojisola; Akinyemi, Abayomi; Assane, Coulibaly; Clamoungou, Clarisse Épse Kaul Meledje; Ndao, Oumy Kalsoum; Kande, Rokhaya Ndiaye; Komeh, James; et al. (Frontiers in Medicine, 2025)
IntroductionWhen implemented by national and regional regulatory agencies good review practices (GRevPs) support the timely high-quality review of medicines for enhanced patients’ availability to safe, quality and efficacious innovative and generic products. It is important that all aspects of GRevPs are continuously evaluated and updated to promote the continuous improvement of regulatory systems at national and regional levels. The aim of this study was to assess and compare the GRevPs of the national medicines regulatory agencies (NMRAs) of Burkina Faso, Cote d’Ivoire, Ghana, Nigeria, Senegal, Sierra Leone and Togo, who are active participants of the ECOWASMRH initiative to identify opportunities for improvement.MethodsThe Optimising Efficiencies in Regulatory Agencies questionnaire, was completed by each of the NMRAs, which facilitates the assessment of GRevPs, which in turn affect the regulatory review processes.ResultsExcept for Cote d’Ivoire and Nigeria which are autonomous, the other five NMRAs operate within the administrative structure of their respective Health Ministry, to regulate medical products for human use, medical devices and diagnostics. Apart from Togo, the agencies receive partial funding from their governments as well as from regulatory fees. Population in the seven countries ranges from 8.6 million to 211.4 million. All the NMRAs had measures in place to achieve quality in their review processes, although there were some remaining initiatives related to transparency and communication, continuous improvement and training and education, to be implemented. Of the ten quality decision-making practices Ghana had implemented nine into a framework, Togo eight, Cote d’Ivoire seven, Nigeria six, and Burkina Faso five; while Sierra Leone has partially implemented all ten and Senegal had not implemented any of the quality decision-making practices.ConclusionThe study compared the organisation, GRevPs and quality decision-making processes of the NMRAs that actively participate in the ECOWAS-MRH initiative. Though some differences were identified with regard to organisation, a significant number of good review practice initiatives and quality decision-making practices were identified yet to be implemented to promote continuous improvement in the regulatory processes of the NMRAs.